Respon Pertumbuhan Dan Hasil Tanaman Sawi Pakcoy (Brassica chinensis L.) Akibat Pemberian Pupuk Kandang Sapi Dan Biourin Sapi - Ni Luh Putu Maheni; I Putu Sujana; Ni Putu Eka Pratiwi (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
Pokcoy mustard is one type of horticultural plant that is easy to cultivate, can grow optimally if they are planted on land that has high enough macro and micro nutrients. This study aims to determine the